2023
DOI: 10.1002/ecs2.4436
|View full text |Cite
|
Sign up to set email alerts
|

The salmonid and the subsurface: Hillslope storage capacity determines the quality and distribution of fish habitat

Abstract: Water in rivers is delivered via the critical zone (CZ)-the living skin of the Earth, extending from the top of the vegetation canopy through the soil and down to fresh bedrock and the bottom of significantly active groundwater.Consequently, the success of stream-rearing salmonids depends on the structure and resulting water storage and release processes of this zone. Physical processes below the land surface (the subsurface component of the CZ) ultimately determine how landscapes "filter" climate to manifest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…Here, we included the percent of the watershed covered by extrusive volcanic rock (V), but it is unclear how broadly this applies to other regions. Similarly, Dralle et al [69] found that underlying geology in the Eel River basin, California, influenced water storage capacity, flow dynamics, vegetation type and canopy cover, all of which subsequently impacted water temperature. The depth of groundwater aquifers can also be important in determining groundwater influence on surface stream temperature [70].…”
Section: Plos Watermentioning
confidence: 90%
“…Here, we included the percent of the watershed covered by extrusive volcanic rock (V), but it is unclear how broadly this applies to other regions. Similarly, Dralle et al [69] found that underlying geology in the Eel River basin, California, influenced water storage capacity, flow dynamics, vegetation type and canopy cover, all of which subsequently impacted water temperature. The depth of groundwater aquifers can also be important in determining groundwater influence on surface stream temperature [70].…”
Section: Plos Watermentioning
confidence: 90%
“…For example, several population model simulations have found reduced salmon spawner abundance resulting from peak flow and temperature increases within the range of our results (Battin et al., 2007; Nicol et al., 2021). Realized impacts to salmon are likely to be context‐dependent, given that flow and temperature affect salmon through complex and non‐linear pathways mediated by local geomorphology (Dralle et al., 2023; Gronsdahl et al., 2019; Sloat et al., 2017), behaviour and physiology (Railsback, 2021) and population dynamics (Ohlberger et al., 2018). While these complexities may further challenge our ability to clearly link forestry activities to salmon population trends (Peacock et al., 2023), our results still provide evidence that forestry poses a risk to salmon systems that in many cases already face an array of other pressures (Munsch et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Above this boundary, groundwater moves laterally through a network of fractures, eventually reaching the stream via seeps and springs (Lovill et al., 2018). The groundwater reservoir can store upwards of 200 mm of dynamic, drainable groundwater (in addition to the catchment‐averaged 300 mm of dynamic storage in the unsaturated soils and rock) that supports year‐round cold baseflows and a thriving salmon population (Dralle et al., 2018; Dralle, Rossi, et al., 2023; Rempe & Dietrich, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The groundwater reservoir can store upwards of 200 mm of dynamic, drainable groundwater (in addition to the catchment-averaged 300 mm of dynamic storage in the unsaturated soils and rock) that supports year-round cold baseflows and a thriving salmon population (Dralle et al, 2018;Dralle, Rossi, et al, 2023;.…”
Section: Field Sitementioning
confidence: 99%